ANALISIS PENERAPAN MANAJEMEN WAKTU PADA PROYEK BANGUNAN PERKANTORAN REVISTAR 3 LANTAI GRAHA DEWATA MALANG - Rhebi, Maria Yoventa; Rasidi, Nawir; Suhudi, Suhudi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Implementation of time management in building projects Revistar III floor Malang Graha Dewata is suatua time management are included in the processes required to ensure completion time proyek. time management centered on whether or not to walk proyek. planning and scheduling in the planning and has provided guidelines penjadawalan specific to the completion of project activities more quickly and efficiently.Where a case study discusses how the implementation of construction projects on time management PT. Edron Yopie Parlindungan is done with the interview, with the study of literature.In the analysis of this study include the scheduling of the project, identification of activities, the preparation sequence of events, the estimated period of time, scheduling, monitoring, recording the performance, analysis, kemajuaan projects in the field, corrective action, and the update schedule, and consideration of existing projects PT. Edron Yopie Parlindungan.From the analysis concluded that the implementation of management time on building projects revistar third floor of Graha Dewata Malang Overall, it was concluded that PT.Edron Yopie Prlindungan good enough in implementing time management system construction project. Keywords: Time Management, Building Projects , Update Schedule Revistar 3 Floor Graha Dewata Malang.